2004
DOI: 10.1080/02827580410019490
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of above ground forest biomass from airborne discrete return laser scanner data using canopy-based quantile estimators

Abstract: ). Estimation of above ground forest biomass from airborne discrete return laser scanner data using canopy-based quantile estimators. Received Nov. 11, 2003. Accepted Aug. 10, 2004. Scand. J. For. Res. 19: 558 Á/570, 2004 A conceptual model describing why laser height metrics derived from airborne discrete return laser scanner data are highly correlated with above ground biomass is proposed. Following from this conceptual model, the concept of canopy-based quantile estimators of above ground forest biomass is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(135 citation statements)
references
References 31 publications
4
130
0
1
Order By: Relevance
“…Nelson et al [70] found that average height, quadratic mean height, and canopy cover accounted for the most of the variation in AGB. Lim and Treitz [77] concluded that laser-based quantiles of canopy heights are useful in predicting forest biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Nelson et al [70] found that average height, quadratic mean height, and canopy cover accounted for the most of the variation in AGB. Lim and Treitz [77] concluded that laser-based quantiles of canopy heights are useful in predicting forest biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that forest inventory variables can be measured and modeled accurately (and precisely) from LiDAR height and density metrics [1][2][3]. These include critical parameters, such as species identification [4], mean diameter at breast height (DBH) [5,6], stand and canopy structural complexity [7,8], forest succession [8], fractional cover [9], leaf area index (LAI) [9,10], crown closure [11], timber volume [6,12,13] and biomass [14][15][16][17]. Estimation of many forest inventory variables using LiDAR data is now moving beyond the research realm and into the operational forum [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include predictive hydrology modeling (Murphy et al 2008, Mandlburger et al 2009), road location optimization and construction (Akay et al 2004, Aruga et al 2005, White et al 2010, harvest block engineering (Chung et al 2004), habitat definition (Clawges et al 2008, Hinsley et al 2008, and timber quantification (Holmgren and Jonsson 2004, Naesset 2004, Parker and Evans 2007. Research conducted specifically in Ontario has focused on estimating forest inventory and biophysical variables for tolerant northern hardwoods (Lim et al 2001(Lim et al , 2002(Lim et al , 2003Todd et al 2003;Lim and Treitz 2004;Woods et al 2008), boreal mixedwoods (Thomas et al 2006(Thomas et al , 2008 and conifer plantations (Chasmer et al 2006). Current acquisition costs, including classification of LiDAR points, derivation of digital elevation models (DEMs) and digital surface models (DSMs), have positioned LiDAR as a potentially operationally affordable alternative when the development of a precision forest inventory is considered a requirement.…”
Section: Introductionmentioning
confidence: 99%